The Meaning and Use of the Modals CAN and MAY in English Contract Law Texts - Lauridsen, Karen M. (HERMES - Journal of Language and Communication in Business, 1992)
This paper presents the results of an analysis of the English modals CAN and MAY in four text types covering the domain of Contract Law. These results show a distinct difference between the two modals, which is interesting because the meaning and use of CAN and MAY is generally taken to be more blurred than it is the case here. The meaning and use of the modals is analysed and compared on the basis of logico-semantic and pragmatic parameters briefly introduced in the paper. The analysis is part of a major contrastive analysis of the meaning and use of the Danish and English modals.